If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2p = -1(2p + -4) Reorder the terms: 4 + -2p = -1(-4 + 2p) 4 + -2p = (-4 * -1 + 2p * -1) 4 + -2p = (4 + -2p) Add '-4' to each side of the equation. 4 + -4 + -2p = 4 + -4 + -2p Combine like terms: 4 + -4 = 0 0 + -2p = 4 + -4 + -2p -2p = 4 + -4 + -2p Combine like terms: 4 + -4 = 0 -2p = 0 + -2p -2p = -2p Add '2p' to each side of the equation. -2p + 2p = -2p + 2p Combine like terms: -2p + 2p = 0 0 = -2p + 2p Combine like terms: -2p + 2p = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 6x-9=7x+3 | | -8(3-2w)=13(2w-12) | | 6x+10=-50 | | 2x-6x=-24 | | 10g^3-25g^2+4g-10=0 | | ky+xz=z | | -5+2x=19 | | 5(2c+6)=7(c-15) | | -10+7x=60 | | xy+kz=z | | -d+1+2d-4= | | h(t)=55 | | 8y^2=8y-1 | | -k+2(5k-6)=-3k-39 | | -4(5-2t)=44 | | 7=13 | | 2a=(4+7)a | | 52=-9+6y-19 | | 38-4e-5+2e=4e-21 | | h(t)=-15t^2+60t+10 | | 11a=14 | | 4x-10=-38 | | 80g^2-45=0 | | x^2-20-2=0 | | Y-6=3y | | 2h^2-2=0 | | 6x^2+29x=-30 | | 6x+2=34 | | 6x^2+28x=-30 | | -5-6x=-41 | | 9+3W=5W+7 | | -75=5(2m-3) |